MicroRNA profiling in post-mortem spinal cord of C9ORF72-related ALS patients reveals molecular pathways involved in motor neuron degeneration - Farinazzo, Giorgia; Giagnorio, Eleonora; Marcuzzo, Matteo; Cattaneo, Marco; Malacarne, Claudia; Cavalcante, Paola; Bonanno, Silvia; Maderna, Emanuela; Pensato, Viviana; Gellera, Cinzia; Marucci, Gianluca; Mazzetti, Samanta; et al. (Frontiers in Neuroscience, 2026)
IntroductionAmyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder causing progressive motor neuron death in cortex, brainstem and spinal cord. The most common genetic cause is the G4C2 hexanucleotide repeat expansion in the non-coding region of exon 1 of C9ORF72, accounting for ~40% of familial and ~7% of sporadic ALS. RNA dysregulation is increasingly recognized as a key contributor to ALS pathogenesis. This study aimed to identify specific microRNAs (miRNAs) involved in motor neuron degeneration in C9ORF72-ALS.MethodsWe profiled 754 miRNAs in human post-mortem spinal cord tissue from C9ORF72-ALS patients and healthy donors. Laser capture microdissection isolated ventral horn regions, and in silico target prediction identified potential genes and pathways regulated by differentially expressed miRNAs. Target genes were validated by Real time PCR.ResultsTwo subsets of miRNAs were exclusively expressed in ventral horn regions: miR-200b-3p and miR-346 in C9ORF72-ALS patients, and miR-30d-5p, miR-106b-5p and miR-135a-5p in healthy donors. Target prediction and molecular analysis identified putative genes and pathways linked to cell death, inflammation, protein metabolism, DNA modification, excitotoxicity, autophagy and vesicles trafficking.DiscussionThis study identifies specific miRNAs and their target genes as key molecules in motor neuron degeneration in C9ORF72-ALS. Restoring their expression could represent a therapeutic approach for ALS.